2014
DOI: 10.3164/jcbn.14-26
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey on lifestyle of patients with nonalcoholic steatohepatitis

Abstract: Lack of exercise and excessive food intake are known to be the important causes of nonalcoholic steatohepatitis (NASH). To elucidate the relationship between lifestyle and NASH, we surveyed exercise and dietary habits, comparing them among 171 biopsy-proven NASH patients, 29 nonalcoholic fatty liver (NAFL) patients and 49 normal subjects. Dietary habits including the duration of dinner time, amount of rice at dinner, and weekly frequencies of meat, fries, Chinese noodles, sweets, and instant food consumption w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“… 18 25 Among them, two had sex-specific data. 22 , 24 As a result, 10 studies were included in the meta-analysis, with 6 cohort 18 22 and 4 case-control studies. 23 25 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 18 25 Among them, two had sex-specific data. 22 , 24 As a result, 10 studies were included in the meta-analysis, with 6 cohort 18 22 and 4 case-control studies. 23 25 …”
Section: Resultsmentioning
confidence: 99%
“…All studies utilized questionnaires for assessment of PA, and the majority of them used ultrasonography for ascertainment of NAFLD except two using liver biopsy. 24 Overall, five studies provided effect estimates adjusted for confounding factors, although the consideration of these factors was different from each study. The methodological quality of included cohort studies was high, with a mean score of 7.7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 14 ) Several cross-sectional studies revealed that regular exercise is associated with a lower NAFLD prevalence. ( 15 19 ) However, the impact of regular exercise on the natural history of NAFLD remains to be elucidated, because there is no large longitudinal study addressing the effect size of regular exercise on remission of NAFLD. Therefore, in this study we investigated a longitudinal analysis of the effect of regular exercise on the natural history of NAFLD in a large-scale Japanese population using standardized ultrasonographic diagnosis for fatty liver as well as standardized questionnaires for lifestyle.…”
Section: Introductionmentioning
confidence: 99%